Tes Frostig untuk Mengukur Kemampuan Visual Anak Berumur 4 - 8 Tahun - Wulan, Ratna (Faculty of Psychology, Universitas Gadjah Mada, 1998)
The purpose of this study is to examine the internal consistency and the reliability of frosting test (marianne frosting development test of visual perception) as a tool to measure visual perception) as a tool to measure visual perception ability of the children age 4-8 years. Person's product moment corrected by part whole and hoyts analysis of variance were used as statistical method.The subjects were 24 male and 26 female children, pupils of kindergartens and primary school in yogyakarta. Results of the study showed that:1. Subtest 1 eye motor coordination, all of the sixteenth items were consisten with the total subtest? coefficient correlation between 0,24 - 0,6372. Subtest II Figure Ground, from 8 items, dropped the first time, coefficient correlation between 0.238-0,8243. Subtest III Constancy of shape, from 32 items dropped 13 items, coefficient correlation between 0,245-0,6284. Subtest IV Position in shae, from 8 items, dropped 13 items, coefficient correlation between 0,245-0,3445. Subtest V Spatial Relationships, from 8 items, dropped the items sumberÂ I and 8, coefficient correlation between 0,357-0,7176. The reliability coefficients of frosting's subtest were 0,813, 0,823, 0,792, 0,54, and 0,7967. The part whole correlation coefficients between score subtest I, II, III, IV, V and total score test were 0,715, 0,763, 0,565, 0,553, Â 0,718 (p<0,01).8. The effective contribution were 34, 165%, 28,759%, 19,960%, 5,928% and 11,188%.Subtest II